Pendidikan Karakter Anak Paroki Katedral Ruteng Melalui Kegiatan Serikat Kepausan Anak Dan Remaja Misioner - Oswaldus Bule; Adriana Aci Sarni; Margareta Vensa Mejang; Felgis Felgis; Maria Yohanista Dhongo (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
The Pontifical Society of Missionary Children is a group prepared to accommodate children and involve them in the life of the church. It becomes a field of socialization and the growth of children in togetherness with others as well as an important means of character building. With the Pontifical Society of Missionary Children in various collective activities that are held regularly every week, the parish becomes more lively and colorful. In addition, The Pontifical Society of Missionary Children activities function to make children creative and full of joy in participating in celebrations in the parish. In the midst of the Covid-19 outbreak, all aspects of life have changed. These changes gave birth to good things, but not infrequently also brought negative things. One of the negative things that emerged from this change in situation was the lack of attention to the development of children's faith in the Church. These resulted in various problems in children such as children living in the midst of a natural and social environment that was less conducive, children less happy and less cheerful. Children became less discipline, less polite, less diligent in praying. In adition, children were passive in activities of faith celebration. We also found these problems in the children in the Cathedral parish of Ruteng. To overcome these problems, we have carried out The Pontifical Society of Missionary Children’s activities for seven meetings. The results of the activity show that there has been a change in the attitude of the child from negative to positive. Therefore, we recommend that this activity be continued and carried out in other places in order to foster healthy, intelligent and high-character children.